Ferrimagnetism and reentrant phenomena in a tetragonal Ising nanoparticle. Issue 17 (1st September 2020) - Kaneyoshi, T.
ABSTRACT: The phase diagrams and magnetizations in a tetragonal Ising nanoparticle have been investigated by using the effective-field theory with correlations and the core–shell model. For the spin-1/2 atoms in the shell, a transverse field is included to cant their spin direction. The results show that they are heavily dependent on the given physical parameters. The ferrimagnetic behaviours, as well as novel type behaviours, have been found in the thermal variation of magnetization. The reentrant phenomena are also obtained.